(untitled) (Baghdad Science Journal, 2011)
This study was carried out in order to determine the toxic, mutagenic and antimutagenic effects for Mallow (Malva parviflora) in comparison to its mutagenic effect of Ultraviolet (UV) because it is consider physical mutagen by using parameters for the extract pri , with , post UV exposure by using bacterial system (G-system). The used system consisted of three isolates G3 Bacillus spp., G12 Arthrobacter spp. and G27 Brevibacterium spp.. The study depended on recording survival fraction (Sx) for studying the effects and induction of Streptomycin and Refampicin resistance mutants as a genetic markers.Water Extract was prepared from fresh and dry mallow leaves, stems, flowers and roots, in optimum concentration equal to (125µg/ml) which is considered a negative control.The interactions included three types of treatments (pre, with and post –UV exposure) as a physical mutagen in order to determine the activity of this plant extracts in preventing or reducing the toxicity of the mutagen. The results of interaction effect between the optimum concentration of water extract and the mutagen on survival fraction (Sx) showed increasing in the value of the survival fraction of G-system isolates to reach normal value in comparison with positive control (UV). The results of the interaction between optimum concentration of extracts and the treatment with mutagen to induce resistance mutant for streptomycin and refampicin showed that the UV had no effect to induce resistance mutant for these two antibiotics, for the two types of treatment (with, post- UV) for all extracts, the water extract suppress or repair mutant and give protection 100% for bacterial cells, while the percentage of pre-UV treatment was (92- 97.3%).